A227 USE OF GBS SCORE, TIME TO ENDOSCOPY, AND PROTON PUMP INHIBITOR USE IN PATIENTS PRESENTING WITH UPPER GI BLEEDING TO THE EMERGENCY DEPARTMENT. (15th March 2019) - Sandha, S; Stach, J; Bullard, M; Halloran, B; Blain, H; Grigat, D; Lang, E; Veldhuyzen van Zanten, S
Abstract: Background: Upper gastrointestinal bleeding (UGIB) is a common presentation to the emergency department (ED) and is associated with significant morbidity and mortality. Early endoscopic intervention within 24 hours has been shown to reduce re-bleeding rates and lower morbidity and mortality. However, low-risk patients can often be managed through outpatient follow-up. Aims: The aim of this study was to compare the timing and appropriateness of endoscopy and proton pump inhibitor (PPI) use in a tertiary care Emergency Department (ED) setting for low and high risk patients determined using the Glasgow Blatchford Score (GBS). Methods: Retrospective chart review was conducted to examine the management of patients presenting with an UGIB in 2016 to the University of Alberta Hospital ED. TANDEM and Emergency Department Information System (EDIS) databases were queried to identify patients using specific ICD-10 codes and the CEDIS presenting complaints of vomiting blood or blood in stool/melena. Patients with GBS from 0 to 3 were categorized as low-risk and those with a GBS > 3 were considered high-risk with: appropriateness of and time to endoscopic intervention, disposition of patient at 24 hours, and use of oral or intravenous (IV) PPIs determined for each group. Results: A total of 400 patients (228 males, mean age 61 years [range 18 to 97 years]) were included. The median GBS was 9. A total of 319/400 patients (80%) underwent esophagogastroduodenoscopy (EGD). Of these, EGD was performed within 24 hours in 37% of patients (29/78) with GBS 0 to 3 and in 77% (248/322) with GBS greater than 3. Of the remaining high-risk patients, 11% (36/322) underwent EGD after 24 hours and 12% (38/322) did not undergo EGD. The endoscopic diagnoses were peptic ulcer disease (PUD) in 41% of patients (130/319), esophagitis in 18% (56/319), and esophageal varices in 14% (45/319). PPIs (data available 375/400) were administered (mainly IV) to 93% (279/300) of high-risk and 79% (59/75) of low-risk patients. Data on patient disposition showed that 60/322 (19%) high-risk patients were discharged from the ED within 24 hours and only 31/60 (52%) of these underwent EGD before discharge. Of 29 low-risk patients undergoing EGD within 24 hours, 9 (31%) were admitted, 17 (59%) were discharged from ED, and 3 (10%) were kept for observation in the ED greater than 24 hours. Of low-risk patients, 76% (59/78) were discharged from the ED within 24 hours. Conclusions: A majority of patients presenting with UGIB appropriately received endoscopy within 24 hours. While most high-risk patients were admitted within 24 hours, 19% were discharged from the ED. 76% of low-risk patients were discharged from the ED within 24 hours. As expected, PPI use was high in these patients. Funding Agencies: PRIHS